Are crossmodal correspondences relative or absolute? Sequential effects on speeded classification. - Brunetti, R; Indraccolo, A; Del Gatto, C; Spence, C; Santangelo, V (Springer, 2017)
Crossmodal correspondences have often been demonstrated using congruency effects between pairs of stimuli in different sensory modalities that vary along separate dimensions. To date, however, it is still unclear the extent to which these correspondences are relative versus absolute in nature: that is, whether they result from pre-defined values that rigidly link the two dimensions or rather result from flexible values related to the previous occurrence of the crossmodal stimuli. Here, we investigated this issue in a speeded classification task featuring the correspondence between auditory pitch and visual size (e.g., congruent correspondence between high pitch/small disc and low pitch/large disc). Participants classified the size of the visual stimuli (large vs. small) while hearing concurrent high- or low-pitched task-irrelevant sounds. On some trials, visual stimuli were paired instead with "intermediate" pitch, that could be interpreted differently according to the auditory stimulus on the preceding trial (i.e., as "lower" following the presentation of a high pitch tone, but as "higher" following the presentation of a low pitch tone). Performance on sequence-congruent trials (e.g., when a small disc paired with the intermediate-pitched tone was preceded by a low pitch tone) was compared to sequence-incongruent trials (e.g., when a small disc paired with the intermediate-pitch tone was by a high-pitched tone). The results revealed faster classification responses on sequence-congruent than on sequence-incongruent trials. This demonstrates that the effect of the pitch/size correspondence is relative in nature, and subjected to trial-by-trial interpretation of the stimulus pair.